Dean Mosman letter to Nicholas S. Halmi regarding bird sightings, November 27, 1977 - Mosman, Deanet al (1977)
Field notes contributed by Dean Mosman in a letter to Nicholas S. Halmi. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1977. Epson - sheet feed/flatbed